Competence Approach to the Formation of Future Specialists’ Communicative Skills in Non-linguistic Educational Institutions. - Лысак, Л. К. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article analyzes the peculiarities of future specialists’ communicative skills formation on the basis of a competence approach in the process of learning the Ukrainian language (for professional purposes). The author focuses attention on the fact that mastering communicative skills of speech communication culture is combined with the development of the all-speech and all-educational abilities based on learning communicative, linguistic and local history aspects